Defatting and Fermentation Treatment on The Bioactive Compounds of Rice Bran - Ramadhan, Febiana Putri; Budijanto, Slamet; Ardiansyah (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Rice bran is a by-product of brown rice milling process. The aim of this study was to determine the effect of fermentation on the changes of total phenolic content, antioxidant activity, and bioactive components in rice bran with the combination of defatting treatment. Coloured rice bran (white, red, and black) was used in this study. Total phenolic content (TPC) and antioxidant activity were analysed with Folin-Ciocalteau and DPPH radical scavenging activity (RSA) method, respectively. Bioactive component of rice bran was analysed by HPLC. The highest TPC and RSA were shown on defatted and fermented white rice bran (288.18±2.52 mg GAE/100 g DB and 67.95±0.75%, respectively). The highest γ-oryzanol content and ferulic acid were shown in non-defatted fermented black rice bran and defatted fermented black rice bran with 24.83 mg/g and 1.45 mg/g sampel, respectively. The results of this study indicated that the fermentation treatment could increase the bioactive component of rice bran. Furthermore, combination of defatting and fermentation was only effective on white rice bran.